The role of radio as the public sphere for public political education in the digital era: Challenges and pitfalls - Anang Sujoko; Dyan Rahmiati; Fathur Rahman (Cogent Social Sciences)
As one of the mass media, the existence of radio in carrying out its role as a social institution to provide education for citizens, especially political education in a democratic country is an interesting topic. The purpose of this study is to analyze the way radio runs and controls political education programs for citizens in public spheres and uncovers radio strategies to survive in the face of competition in the digital era. This study adopted descriptive qualitative methods and qualitative content analysis using radio interactive programs. The data were collected through interviews with the manager or directors of each radio. The subjects of this study were four radio stations in East Java, Indonesia. The results showed that radio carries out this role by organizing programs that involve participants. All radios have a mechanism for selecting participants, news and experts/informants. In carrying out its function as a social institution to provide education for citizens including political education, radio has made serious efforts by producing content that: 1) provides knowledge about local political dynamics; 2) criticizes public policies; and 3) activates citizen participation in public issues. Selectively choose the content of the program. Radio’s ability to survive was strongly supported by its ability to utilize of income opportunities and elegantly avoid economic and political pitfalls by empowering the role of the public sphere through massive involvement of external sources. Thus, the constructed opinion seems to be more of an extra media influence rather than an internal initiative of the radio organization.